Efficacy in the field of two anticoccidial vaccines for broilers - Guido Grilli; Daniele Gallazzi; Luigi Gavazzi; Viviana Ferrazzi; Raffaella Ceruti (Italian Journal of Animal Science, 2010)
We compared two attenuated anticoccidial vaccines, administered to broilers by spray into the incubator (88,000 males and 210,100 females). Vaccine A container five species of Eimeria and vaccine B three. Zootechnical performance was similar in the two groups, with mean lesion scores no higher than 1; vaccine A caused only duodenal lesions, while vaccine B also caused typhlitis. Maximum oocyst count was 23,000/g feces at age 28 days with vaccine A and 38,000 at 21 days with vaccine B. Broilers vaccinated with vaccine B had more frequent enteric symptoms, and C. perfringens isolation.